2018
DOI: 10.5114/ceji.2018.81354
|View full text |Cite
|
Sign up to set email alerts
|

Natural antibodies – facts known and unknown

Abstract: In contrast to adaptive antibodies, natural antibodies are present in a non-immunised organism from birth, and they do not include anti-Gal antibodies and/or anti-Gal natural antibodies, which are developed as a result of the effect of the α-Gal epitope and physiological flora. Natural antibodies are the first line of the organism’s defence before the formation of the immunity created via the stimulation of elements that determine specific and non-specific immunity. This is especially important in the case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 105 publications
3
86
0
3
Order By: Relevance
“…Why this particular response occurs is unclear. Based on existing studies (Avrameas and Selmi, 2014;Palma et al, 2018), it may involve different levels of natural autoantibodies that may directly be linked to a different embryonic (perinatal) thymus exposure to the endogenous HERV-W envelope, which would be decreased or defective in such individuals. Moreover, it should be relevant to note that the antibody response we documented in the study does not have the magnitude of antibody response to infectious agents, when the adaptive immune system is involved in an antibody response to exogenous antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Why this particular response occurs is unclear. Based on existing studies (Avrameas and Selmi, 2014;Palma et al, 2018), it may involve different levels of natural autoantibodies that may directly be linked to a different embryonic (perinatal) thymus exposure to the endogenous HERV-W envelope, which would be decreased or defective in such individuals. Moreover, it should be relevant to note that the antibody response we documented in the study does not have the magnitude of antibody response to infectious agents, when the adaptive immune system is involved in an antibody response to exogenous antigens.…”
Section: Discussionmentioning
confidence: 99%
“…When such a response is directed against self-tissues, autoimmunity may ensue. However, healthy individuals can have signatures of autoimmune response as evidenced by the detection of low levels of antibodies and T cells against autoantigens that may reflect formation of natural antibodies or idiotypic networks [1][2][3][4]. Autoimmune diseases (AIDs) are clinically manifested when autoimmunity leads to tissue damage disrupting the functions of affected organs [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that sera of patients with or without autoimmune diseases contain IgG autoAbs that react with a set of self-antigens and are unique to each disease [7,8]. These so-called natural autoAbs usually react with intracellular proteins and long non-coding RNAs, and are thought to have evolved as an adaptive mechanism for functions such as debris clearance, which is consistent with their utility as diagnostic and prognostic indicators of disease [8].…”
Section: Introductionmentioning
confidence: 82%
“…For about 50 years since the discovery of natural IgG autoAbs, it was generally thought that they had a low affinity for autoantigens; therefore, the role of natural IgG autoAbs has remained unclear [7]. However, recent studies have revealed that natural IgG autoAbs are not non-reactive, rather they have a fundamental role in systemic innate immune responses [8].…”
Section: Autoimmune Pulmonary Alveolar Proteinosismentioning
confidence: 99%